Edukasi Kehamilan Risiko Tinggi melalui Media Permainan Ular Tangga di Kelas Ibu Hamil: High-risk Pregnancy Education through Snakes and Ladders Game in Antenatal Class - Nurlaili, Helmi; Istikhomah, Henik; Susilowati, Dewi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
One of the action plans for the acceleration of maternal mortality rate reduction is ensuring that every mother can access quality health services. Low maternal knowledge in recognizing obstetric and neonatal danger signs results in late decisions to get medical help. Maternity classes are to provide knowledge to pregnant women and their families. The learning method through the Snakes and Ladders game is expected to increase the active participation of pregnant women and communicate with other pregnant women. This activity was conducted on August 5, 2024, to 15 pregnant women in the Maternal Class in Masaran Village, Sragen Regency. The Snakes and Ladders game requires a banner as a game board, dice, and question cards. Pregnant women's knowledge about high-risk pregnancy was analyzed through pre and post-test questionnaires. Pregnant women looked enthusiastic during the game. Representatives of each group completed the game. Other members got involved by providing answers according to the questions their group got. Some pregnant women asked questions after the game was over. Wilcoxon pre and post-test of the Snakes and Ladders game obtained a value of ρ = 0.001. It is concluded that education through the Snakes and Ladders game is proven to improve pregnant women's knowledge about high-risk pregnancy.